Analysis of the editorial policies of legal journals in Latin America in Spanish with open access in Scopus - Pezo Jimenez, Omar; Bellodas Ticona, Carlos Augusto; Peñaloza de la Torre, Vanessa Catherine (Revista General de Información y Documentación, 2025)
Research is a task of vital importance, and for this it is necessary to be able to provide an overview of the guidelines that scientific journals have in order to publish articles; especially when there is a wide range of magazines of this nature. This in order to optimize and strengthen research. Therefore, the objective of this work is to analyze the editorial policies of open access law journals in Latin America in Spanish in Scopus. The work of the magazines was carried out regarding the topics of nationality, quartiles, periodicity, number of authors allowed, type of citation, processing charges and disciplines published by the magazine. Concluding that this research stands as a bibliometric tool for the service of the legal and scientific community, where they can verify their policies
Keywords: Law; open access; bibliometrics; scientific journal; scientific research